DAMPAK PANDEMI COVID-19 TERHADAP PERILAKU KONSUMSI PARIWISATA: STUDI EMPIRIS PADA WISATAWAN DOMESTIK INDONESIA - Lis Andriani; Muji Rahmat Ramelan; Yuniarti Fihartini (Faculty of Economics and Business University of Lampung, 2021)
The Covid-19 pandemic has had an impact on all economic sectors, including the tourism industry and its supporting sectors. The pandemic has changed people's views of travel, behavior in choosing tourist destinations, and determining of the tourism consumption decisions. Meanwhile, the sustainability of the tourism industry highly depends on the flow of tourists and the perception of individual tourists. This study identifies the tourist attitudes regarding hygiene and safety factors,identifies the tourist behavior in consuming of the tourism, and identifies tourism potential both during and after the Covid-19 pandemic. This research was conducted using a survey method through an online questionnaire to 353 respondents. Hypotheses testing was done using descriptive statistical technique which is one sample t-test using SPSS. The results show that all hypotheses in this study can be supported.Travelers consider it very important to implement health protocols during thepandemic. The pandemic has not stopped tourists from taking trips, however the tourists tend to postpone their plans to the destinations with high Covid-19 virus infections. They avoid crowded destinations, prefer culinary tours and outdoor attractions near their residential areas, and avoid group trips. Original nature-based tourism objects (ecotourism, maritime, marine) and agriculture-based (agrotourism) that offer privacy and customization are considered potential to be developed during and after the pandemic. Keywords: Tourist Destinations, Tourism Consumption, Tourist Behaviour, Hygiene and Safety